Media Pembelajaran Pemasangan Kontrasepsi Implan terhadap Pengetahuan dan Keterampilan Mahasiswa Kebidanan - Susilawati, Enny; Sari, Lia Artika; Nugraheni, Diah Eka; Pulungan, Verawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the influence of e-books and Augmented Reality learning media for installing contraceptive implants on the knowledge and skills of midwifery students. The method used is experimental, using a one-group pre-test and post-test design, with the development of e-book media products containing text, images, sound, and augmented reality. The research results showed that there was a significant influence on knowledge and skills before and after the use of e-book learning media and Augmented Reality for installing contraceptive implants in midwifery students (p = 0.000). The research conclusion is that e-books and Augmented Reality learning media for installing contraceptive implants are effective in improving the skills of midwifery students. Keywords: Learning Media, E-Book, Augmented Reality, Installation of Implant Contraception